Trade and industrial policy of Ecuador - ZARATE DIAZ, Paul Marcelo (KDI School, 2021)
Ecuador has executed various industrial policies during the XX century with different focuses and results. Still, none of them could achieve the primary purpose, “creating a prosperous and developed nation.” Currently, Ecuador has in force the “Industrial Policy 2016- 2025.” However, it is not under execution since there is a disconnection between the projects, goals, and strategies with Ecuador''s competitive advantages and future global demands and trends. Besides, Ecuador does not have a formal trade policy; instead, the Ministry of Production, Foreign Trade, Investments, and Fisheries are executing trade agendas trying to sign free trade agreements with key commercial partners. Still, those agreements aim to take advantage of the current economic structure of Ecuador, which is characterized for promoting agriculture products, low-skill jobs, and no innovation. In this regard, this research describes a new approach of trade and industrial-innovation policy, outlining factors that determine its success or failure. Moreover, the study revised up-to-date bibliography to identify characteristics for increasing the odds for designing and executing trade and industrial-innovation policies. Besides, it describes the actors and roles that must develop the design and execution of the policy. Finally, a logical framework matrix is presented with general activities that will guide the update of the current industrial policy, to build a new approach for the insertion of Ecuador to the 21st century. The principal findings of the research show that the current industrial policy of Ecuador is not efficient and must be updated. The trade agenda should be transformed into a policy integrated into the industrial one. Moreover, for the updating, the Government should consider factors such as climate change, COVID-19, political issues like the trade war between China and the United States, the structure of a new global economy by 2050, and the rise of the African Free Trade Agreement. All those situations bring about opportunities and threats that must be tackled with a long-term, adequately financed innovation policy, structured after discussions with the private sector, academia, and civil society. Indeed, the new trade and industrial policy should be the outcome from communication with different actors instead of being a set of top-down actions proposed by the public sector. Finally, the trade policy must be built in concordance with the industrial policy and focused not only on the current supply but also on the future international demands and needs.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Commercial policy--Ecuador